The Effect Of Nanoherbal Solanum Lycopersicum On Rat Induced Streptozotocin - Djohan Djohan; Bungaran Sihombing; Sahna Ferdinand; Hanjaya Hanjaya (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
Abstract : Diabetes Mellitus (DM) has become a global health threat in the 21st century. DM sufferers are increasing, according to the International Diabetes Federation (IDF) in 2017, the number of DM sufferers in the world is 7.5 million people and is predicted to be 9.5 million in 2017. In 2045, Indonesia itself was ranked 7th out of 10 countries with the most DM at the age of 20-79 years and ranked 4th out of 10 countries with the largest population of undiagnosed. This study aim to determine the antihyperglycemia activity of Nanoherbal Extract of Solanum lycopersicum. This is an experimental study in which the research group was divided into seven groups, each including five rats weighing 200-250 grams. Which are (normal group, negative group, metformin, nanoherbal 25, 50, 100, and 200 mg/kgBW). Rats were induced by STZ 55 mg/kgBW + NCT 120 mg/kgBW until the blood glucose is above 200 mg/dL. The highest level of SOD is the control group 63.984 ± 2,065 ng/mL and the lowest is negative group is 18,173 ± 2,130 ng/mL. For group that given treatment show that the highest SOD level is in dose 200 mg/kgBW 77,603 ± 3,089 ng/mL and the lowest is in dose 25 mg/kgBW 33,612 ± 1,477 ng/mL and the group given metformin is 69,546 ± 3,128 ng/mL. The highest level of Insulin is the control group 305,573 ± 5,51ng/mL and the lowest is negative group is 48,5366 ± 2,44 ng/mL. For group that given treatment show that the highest insulin level is in dose 200 mg/kgBW 305,939 ± 4,999 ng/mL and the lowest is in dose 25 mg/kgBW 73,938 ± 4,38 ng/mL and the group given metformin is 300,176 ± 10,072 ng/mL. Nanoherbal of Solanum lycopersicum has antihyperglycemia activity by increasing the level of insulin and SOD.